Social Capital Values as the Strengthening Elements in the Rural Small Industry - Kimbal, Rahel Widiawati; Tangkau, Jaqueline E.M (Journal of International Conference Proceedings, 2021)
This research aims at revealing various practices of social capital values to strengthen rural small industry. The practices which emerge from the interaction among farmers, big vendor, tibo, roasted nut business owner and consumers lead to different forms of social capital values. This research uses qualitative research method which involves a study case. The data are analyzed using forward stepwise model from Spradley, which formulates the findings from the empirical research. The research findings reveal various social capital values embedded in local tradition of Minahasa known as Mapalus. It refers to a form of cooperation which grow and develop among the Minahasans. Mapalus includes various social activities as follows (1) Mendu impero’ongan, a community service performed by the villagers; (2) Berantang, providing help for the bereaved family; (3) Sumakey, celebrating certain occasions together. Mapalus also exists in economic and financial activities such as: (1) Ma’endo. It refers to communal activities to cultivate the field or to renovate houses; and (2) Pa’ando. It is a financial activity in a form social gathering known as ‘arisan’. This cultural value is an important social capital for rural society to support their economic activities and to strengthen the rural small industry.